Benefits of Chemical Sugar Modifications Introduced by Click Chemistry for Glycoproteomic Analyses - Calle, Beatriz; Bineva-Todd, Ganka; Marchesi, Andrea; Flynn, Helen; Ghirardello, Mattia; Tastan, Omur Y.; Roustan, Chloe; Choi, Junwon; Galan, M. Carmen; Schumann, Benjamin; Malaker, Stacy A. (Journal of the American Society for Mass Spectrometry, 2021)
Mucin-type O-glycosylation is among the most complex post-translational modifications. Despite mediating many physiological processes, O-glycosylation remains understudied compared to other modifications, simply because the right analytical tools are lacking. In particular, analysis of intact O-glycopeptides by mass spectrometry is challenging for several reasons; O-glycosylation lacks a consensus motif, glycopeptides have low charge density which impairs ETD fragmentation, and the glycan structures modifying the peptides are unpredictable. Recently, we introduced chemically modified monosaccharide analogues that allowed selective tracking and characterization of mucin-type O-glycans after bioorthogonal derivatization with biotin-based enrichment handles. In doing so, we realized that the chemical modifications used in these studies have additional benefits that allow for improved analysis by tandem mass spectrometry. In this work, we built on this discovery by generating a series of new GalNAc analogue glycopeptides. We characterized the mass spectrometric signatures of these modified glycopeptides and their signature residues left by bioorthogonal reporter reagents. Our data indicate that chemical methods for glycopeptide profiling offer opportunities to optimize attributes such as increased charge state, higher charge density, and predictable fragmentation behavior.
Keywords: Chemically modified; Click chemistry; Consensus motif; Fragmentation behavior; Glycan structures; Physiological process; Post-translational modifications; Tandem mass spectrometry; Click Chemistry; Glycopeptides; Glycosylation; Mucins; Protein Processing, Post-Translational; Proteomics; Sugars; Tandem Mass Spectrometry; bioorthogonal; click chemistry; ETD; glycopeptide; glycoproteomics; mucin